Safety and efficacy of a feed additive consisting of manganese chelate of ethylenediamine for all animal species (Zinpro Animal Nutrition (Europe), Inc.). (22nd March 2021) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Durjava, Mojca Fašmon; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of manganese chelate of ethylenediamine (Manganese‐EDA‐Cl) as feed additive for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) identified several issues related to the data provided concerning the chemical characteristics of the additive. Based on the information provided, the FEEDAP Panel considered unlikely that the additive consists only of manganese mono‐chelate of EDA, but of several coexisting (manganese) species; therefore, the FEEDAP Panel was unable to confirm the identity of the additive. The FEEDAP Panel could not evaluate the safety for target species, consumer and environment and the efficacy of the additive owing to the uncertainties and limitations identified in the studies submitted. Concerning the safety of the additive for the users, the Panel considered that handling the additive poses a risk to users by inhalation. The additive should be considered as corrosive to eyes and a skin sensitiser.